1985
DOI: 10.1038/bjc.1985.271
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year follow-up of all patients in a study of post-operative chemotherapy for bronchial carcinoma

Abstract: Plan and conduct of the studyThe plan and conduct of the study were described in detail previously (Medical Research Council, 1971). In summary, after resection of all intrathoracic bronchial tumour, the patients were allocated at random to receive tablets of busulphan (B series), cyclophosphamide (C series), or indistinguishable placebos (P series) daily for 2 years. For the first 10 days following operation, all patients received 8 tablets in a single daily dose (B series 4 mg, C series 200 mg). Thereafter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Thirty three of these were found to be ineligible and therefore excluded (appendix 1). Of the 58 eligible trials13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 (Lung Cancer Study Group protocol 853, unpublished data; M Imaizumi, personal communication; Finnish Lung Cancer Study Group, unpublished data; European Organisation for Research and Treatment of Cancer protocol 08861, unpublished data; G Anderson, personal communication; European Organisation for Research and Treatment of Cancer protocol 08842, unpublished data; South Western Oncology Group protocol 8300, unpublished data), data were not available from six as they had been lost or destroyed or were untraceable25 26 49 50 51 52 (appendix 1). Data from 52 randomised trials and 9387 patients were therefore included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty three of these were found to be ineligible and therefore excluded (appendix 1). Of the 58 eligible trials13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 (Lung Cancer Study Group protocol 853, unpublished data; M Imaizumi, personal communication; Finnish Lung Cancer Study Group, unpublished data; European Organisation for Research and Treatment of Cancer protocol 08861, unpublished data; G Anderson, personal communication; European Organisation for Research and Treatment of Cancer protocol 08842, unpublished data; South Western Oncology Group protocol 8300, unpublished data), data were not available from six as they had been lost or destroyed or were untraceable25 26 49 50 51 52 (appendix 1). Data from 52 randomised trials and 9387 patients were therefore included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The Lung Cancer Study Group in the USA (20) reported that postoperative radiotherapy did not increase survival rates in cases with complete resection for stages I1 and 111 squamous cell carcinoma in a randomized trial. Other studies (21)(22)(23) also showed negative results in selected patients. We could not see any beneficial effect from perioperative adjuvant radio-/chemotherapy on the prognosis in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…366 In a prospective 15-year evaluation of 726 patients with lung cancer treated with busulfan, cyclophosphamide, or placebo, no additional malignancies were seen in the cyclophosphamide arm above the placebo rate. 360 CHF, hemopericardium, and hemorrhagic myocarditis have been seen after high doses of cyclophosphamide. These side effects usually resolve after stopping therapy.…”
Section: Information For Patientsmentioning
confidence: 99%
“…324,359 Table 29 summarizes the adverse events encountered with cyclophosphamide. 352,357,[360][361][362] Table 30 summarizes seven studies of cyclophosphamide for various lung diseases, 324,352,355,357,360,363,364 and Table 31 summarizes one study in which cyclophosphamide was used for nonpulmonary disease but has important information regarding toxicity. 358 3.5.2.1 Toxicity-Hemorrhagic cystitis is seen with cyclophosphamide therapy and can occasionally be severe or fatal.…”
Section: Cyclophosphamidementioning
confidence: 99%